Kontribusi Pimpinan Ranting Muhammadiyah Perintis di Masjid Taqwa Muhammadiyah terhadap Sikap Sosial - Arlina, Arlina; Sriwahyuni Pasaribu; Habibie Ramadhan; Rini Antika Sari Rangkuti; Darma Syahputra Hasibuan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this research is to find out the activities at the Taqwa Muhammadiyah mosque, especially in terms of social attitudes. This research uses qualitative methods, with data collection techniques in the form of observation, interviews and documentation with the aim of collecting and strengthening research data. The subjects of this research were the people around the mosque and several leaders of the Muhammadiyah Pioneer Branch. By using data validity techniques, namely long term, long term and triangulation. The results of the research show that there are many activities that have been taking place, especially in forming social attitudes in society, namely supporting orphans and the poor, increasing knowledge by holding recitations, breaking the fast together and sharing takjil, mutual cooperation by cleaning the mosque together.